From transients to permanent residents: the existence of obligate aerobic microorganisms in the goat rumen - Wang, Rongjiao; Huang, Dan; Chen, Changguo; Song, Dingzhou; Peng, Hongen; He, Min; Huang, Xiujun; Huang, Zhonghua; Wang, Bin; Lan, Hai; Tang, Ping (Frontiers in Microbiology, 2024)
The rumen serves as a complex ecosystem, harboring diverse microbial communities that play crucial ecological roles. Because previous studies have predominantly focused on anaerobic microorganisms, limited attention has been given to aerobic microorganisms in the goat rumen. This study aims to explore the diversity of aerobic microorganisms in the rumen and understand their niche and ecological roles. Rumen fluid samples were collected from 6 goats at different time points postmorning feeding. pH, NH3-N, and volatile fatty acid (TVFA) concentrations were measured, while In vitro cultivation of aerobic microorganisms was performed using PDA medium. Internal Transcribed Spacer (ITS) and 16S sequencing unveiled microbial diversity within the rumen fluid samples. Evidence of obligate aerobic microorganisms in the goat rumen suggests their potential contribution to ecological functionalities. Significantly, certain aerobic microorganisms exhibited correlations with TVFA levels, implying their involvement in TVFA metabolism. This study provides evidence of the existence and potential ecological roles of obligate aerobic microorganisms in the goat rumen. The findings underscore the significance of comprehensively deciphering goat rumen microbial communities and their interactions, with aerobes regarded as permanent residents rather than transients.These insights form a solid foundation for advancing our understanding of the intricate interplay between goat and their aerobic microorganisms in the rumen.